The Politics of Fear and Attention: The Platform Logic of Democratic Erosion - Merkovity, Norbert (POLARITIES, 2025)
This article examines how fear and attention intersect as structuring forces in contemporary political communication. Grounded in symbolic interactionism, media logic, attention-based politics, and the concept of fear as infrastructure, this conceptualization theorizes fear as an affective mechanism embedded in platform environments. Selected examples from the communication style of Donald Trump and Viktor Orbán serve as brief illustrations of how these dynamics appear in practice, rather than as systematic case studies. The analysis reveals that fear serves as a performative resource, shaping community boundaries, legitimizing leadership, and organizing political visibility. The convergence of fear and attention reshapes political identity, amplifies polarization, and challenges the normative foundations of democratic communication.